1988
DOI: 10.1017/s0016672300024265
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of the initiation of DNA replication in stringent and relaxed strains ofEscherichia coli

Abstract: Starvation for isoleucine inhibits chromosome, minichromosome and pBR322 DNA replication in a stringent strain of E. coli, but does not do so in a relaxed mutant. Starvation for other amino acids inhibits either chromosome and minichromosome replication in both strains. From these results we conclude that oriC and pBR322 replication are stringently regulated and that isoleucine seems not to be essential for the protein synthesis required at the initiation of oriC replication. Deprivation of isoleucine in a Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Recently these results were confirmed by Guzman et al (1988) who found that deprivation of isoleucine in a Rel" strain gives rise to amplification of pBR322 with a better yield than that following treatment with chloramphenicol (Hecker et al, 1985). The results of this study give further evidence that E. coli relA strains are able to amplify ColElrelated plasmids.…”
Section: Introductionsupporting
confidence: 74%
“…Recently these results were confirmed by Guzman et al (1988) who found that deprivation of isoleucine in a Rel" strain gives rise to amplification of pBR322 with a better yield than that following treatment with chloramphenicol (Hecker et al, 1985). The results of this study give further evidence that E. coli relA strains are able to amplify ColElrelated plasmids.…”
Section: Introductionsupporting
confidence: 74%
“…This was expected, because we have previously shown that this promoter is stringently controlled and inhibited by ppGpp (45,46), and stringently controlled promoters are also growth rate regulated (13). In Bacillus subtilis, induction of the stringent response leads to an inhibition of chromosomal replication (51); indications are that this is also true for E. c oli (26,51), so a component of the initiation machinery appears to respond to changes in ppGpp concentrations in manner similar to that of rRNA operons.…”
Section: Discussionmentioning
confidence: 77%
“…Replication of E. coli chromosome as well as oriC plasmids is inhibited during stringent response whereas in retA mutants, the replication proceeded when bacteria were starved for isoleucine but not for other amino acids (GUZMAN et al 1988, LEVINE ef al. 1991.…”
Section: Oricmentioning
confidence: 99%
“…Changes in transcription efficiency from many promoters are primary effects of ppGpp action. Although differences between DNA replication in amino acid-starved relA+ and relA-strains were demonstrated, these results were often controversial; in some cases starvation for a particular amino acid gave different results than for another one (GUZMAN et al 1988, HECKER et al 1983, 1985, HERMAN et al 1994a, b, LIN-CHAO and BREMER 1986, RIETHDORF et al 1989, W~GRZYN et al 1991a). Since ppGpp is the main effector of the stringent response (CASHEL and RUDD 1987) only investigation of the process in unstarved cells containing increased levels of ppGpp could eliminate the secondary effects of amino acid deprivation and allow to answer the following question: is DNA replication under stringent control?…”
mentioning
confidence: 99%